2003
DOI: 10.1034/j.1600-0420.2003.00129.x
|View full text |Cite
|
Sign up to set email alerts
|

Chronic angle closure glaucoma secondary to frail zonular fibres and spherophakia

Abstract: ABSTRACT.Purpose: We describe a 39-year-old Japanese woman with chronic angle closure glaucoma secondary to spherophakia and frail zonular fibres. The patient was 143 cm in height with short fingers and had no family history of eye problems. High intraocular pressure, total optic disc cupping and severe visual field constriction were found in the right eye. Case ReportA 39-year-old Japanese woman presented with decreased vision in her right eye on June 7, 2000. She had suffered high myopia bilaterally since c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
16
0

Year Published

2006
2006
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 23 publications
(17 citation statements)
references
References 9 publications
0
16
0
Order By: Relevance
“…Two modes of inheritance have been reported: autosomal dominant (OMIM #608328) and autosomal recessive (OMIM #277600) [Faivre et al, 2003a]. The diagnosis is based on the clinical manifestations since there is no biochemical test or histological marker [Dietlein et al, 1998;Asaoka et al, 2003]. Recently, mutations in ADAMTS10 (in autosomal recessive cases) and in FBN1 (in autosomal dominant cases) have been reported in some WMS patients [Dagoneau et al, 2004].…”
mentioning
confidence: 96%
“…Two modes of inheritance have been reported: autosomal dominant (OMIM #608328) and autosomal recessive (OMIM #277600) [Faivre et al, 2003a]. The diagnosis is based on the clinical manifestations since there is no biochemical test or histological marker [Dietlein et al, 1998;Asaoka et al, 2003]. Recently, mutations in ADAMTS10 (in autosomal recessive cases) and in FBN1 (in autosomal dominant cases) have been reported in some WMS patients [Dagoneau et al, 2004].…”
mentioning
confidence: 96%
“…However, Yasar (2003) described a patient in whom lensectomy could control the IOP in the short-term, but who subsequently required trabeculectomy. Asaoka et al (2003) reported successful control of IOP with trabeculectomy in a patient with spherophakia and open angles . Kaushik et al (2006) reported that pupillary block can be relieved by lensectomy, but it may not suf¿ ce to control the IOP in the presence of extensive PAS.…”
Section: Discussionmentioning
confidence: 99%
“…IOP elevation in spherophakia can occur by a variety of mechanisms (Willoughby and Wishart, 2002;Kaushik et al, 2006;Asaoka et al, 2003). Angle-closure glaucoma occurs in spherophakia from a pupillary block mechanism caused by dislocation or forward movement of the lens, depending on the zonular integrity.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…8 WeillMarchesani syndrome has been associated with other systemic problems such as thick skin, a muscular build, cardiac abnormalities, and mental retardation. 1,9 At present, the diagnosis of the syndrome is on the basis of clinical manifestations and there are no biochemical or histologic specifications that confirm the syndrome. 9,10 Despite clinical homogeneity, 2 modes of inheritance have been reported: autosomal dominant and autosomal recessive.…”
mentioning
confidence: 98%